Air-blast response of cellular material with a face plate: An analytical–numerical approach. (February 2015) - Aleyaasin, M.; Harrigan, J.J.; Reid, S.R.
Abstract: The air-blast response of a sacrificial cladding consisting of a cellular material with a front face-plate is investigated. The cellular material is sandwiched between a rigid face-plate and a rigid support. The support represents the structure that is to be protected. The air blast is assumed to be an exponentially decaying pulse. The cellular material is idealised as rigid, perfectly-plastic, locking and the deformation is governed by the propagation of a compaction (shock) wave travelling through the material. A second order nonlinear ordinary differential equation is derived to predict the displacement of the face-plate and the compression of the cellular layer by coupling the reflected over-pressure with the stresses at the interface between the face-plate and the cellular material. The cellular material may attenuate or enhance the shock transmitted to the structure. Extensive simulations are carried out to define the attenuation/enhancement boundary for a range of initial peak pressures and cladding parameters. Herein, enhancement is considered to occur if the shock front reaches the support. A new method of accounting for fluid–structure interaction (FSI) is derived. The predictions are compared to those with no FSI as well as an existing model that accounts for the FSI effect, but for a free-standing plate. Highlights: The response of a cellular material and a solid face-plate subjected to air blasts is analysed. A new fluid structure interaction (FSI) model is developed to predict reflected overpressure. Contours are presented for the attenuation/enhancement boundary of such a sacrificial cladding.